Analyzing the Impact of Personal Scorecards, Organizational Commitment, Functional Competence, and Managerial Competence on Financial Management Employee Performance - Amri, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aimed to assess and examine the impact of personal scorecards, organizational commitment, functional competence, and managerial competence on the performance of financial management personnel. The study population consisted of all employees (n = 99) employed at the Makassar City Financial and Asset Management Agency. Sixty individuals were included in this study, as determined by using the Slovin formula. The primary data source is information researchers directly obtain from respondents using questionnaire tools. The proposed data analysis approach encompasses several key components, including descriptive statistical analysis, validity testing, reliability testing, normality testing, heteroscedasticity testing, multicollinearity testing, and hypothesis testing using multiple linear regression analysis. Additionally, the research will involve conducting partial tests, simultaneous tests, and determination coefficient tests. This study's findings suggest a statistically significant and positive relationship between personal scorecard variables, organizational commitment, functional competence, and managerial competence, and the performance of financial management employees at the Makassar City financial and asset management agency.